Metagenomic Identification of Novel Eukaryotic Viruses with Small DNA Genomes in Pheasants - Kaszab, Eszter; Bali, Krisztina; Marton, Szilvia; Ursu, Krisztina; Farkas, Szilvia L.; Fehér, Enikő; Domán, Marianna; Martella, Vito; Bányai, Krisztián (Animals (Basel), 2024)
A panel of intestinal samples collected from common pheasants (Phasianus colchicus) between 2008 and 2017 was used for metagenomic investigation using an unbiased enrichment protocol and different bioinformatic pipelines. The number of sequence reads in the metagenomic analysis ranged from 1,419,265 to 17,507,704 with a viral sequence read rate ranging from 0.01% to 59%. When considering the sequence reads of eukaryotic viruses, RNA and DNA viruses were identified in the samples, including but not limited to coronaviruses, reoviruses, parvoviruses, and CRESS DNA viruses (i.e., circular Rep-encoding single-stranded DNA viruses). Partial or nearly complete genome sequences were reconstructed of at least three different parvoviruses (dependoparvovirus, aveparvovirus and chaphamaparvovirus), as well as gyroviruses and diverse CRESS DNA viruses. Generating information of virus diversity will serve as a basis for developing specific diagnostic tools and for structured epidemiological investigations, useful to assess the impact of these novel viruses on animal health.